Gaze and Recipient Feedback in Triadic Storytelling Activities. Issue 9 (20th October 2020) - Zima, Elisabeth
ABSTRACT: This article focuses on the relationship between gaze and recipient feedback in triadic storytelling activities. Our starting point to investigate this relationship is an article by Bavelas et al. (2002), who report a statistically significant interaction between feedback and so-called gaze windows in dyadic storytelling activities. The pattern they found involves three interdependent phases: a narrator shifts gaze to a recipient to elicit feedback (phase 1), narrator and recipient are mutually gazing at each other while the recipient gives feedback (phase 2), and the narrator shifts gaze away from the recipient (phase 3). In our triadic data, where gaze was captured by mobile eye tracking glasses, gaze is equally used to elicit feedback. However, feedback is most often not produced during mutual gaze between narrators and recipients. The gaze window pattern is instantiated in only roughly one third of the feedback tokens in our corpus. We illustrate coexisting gaze patterns and discuss reasons why mutual gaze between narrator and feedback-giving recipient is less prevalent in our data.